The boy next story - Schmidt, Tiffany (Schmidt, Tiffany. Bookish boyfriends., 2019)
Aurora Campbell is fourteen and has been in love with Tobias May, the boy next door, ever since they shared a kiss in the sandbox--but Tobias is in love with Merrilee, Aurora's older sister, and Merrilee is dating one of Tobias' best friends. Aurora, meanwhile, has to worry about her GPA and improving her grades if she wants to win the chance to spend winter break studying art in New York City. To do so, her teacher assigns her to read "Little Women," and reading that helps Rory realize she maybe isn't as in love with Tobias as she might have thought.